Studies On The Effects Of Graded Doses Of Nitrogen , Phosphorus And Potassium On Growth , Yield And Quality Of Bhindi - Subramanian KV (Department of Olericulture, College of Horticulture, 1980)
The yield of bhindi per unit of land and per unit of time has been observed to be very low in our country. A galaxy of reasons- poor genetic potential of the existing genotypes, incidence of parasitic and non- parasitic diseases and above all lack of an appropriate agronomic practices – have been attributed to the poor performance of Indian bhindi. There remains an urgent need to chalk out a fertilizer schedule for the high yielding varieties like Co.I which is popular in Kerala. The present study “studies on the effect of graded doses of nitrogen, phosphorus and potassium on growth, yield and quality of bhindi (Abelmoschus esculentus (L.) Moench.)”, was designed to find out the optimum and economic levels of the three major nutrients (nitrogen, phosphorus and potassium) which would give a yield level above 100 g/ha. A significant increase in yield was observed due to increasing levels of all the three nutrients. In the case of nitrogen the yield was found to increase upto 60 kg/ha and the economic and optimum levels were worked out to be 61 and 61.23 kg/ha respectively. Response to phosphorus and potassium application was observed to be linear. Patterns in uptake of nutrients indicated that a bhindi crop yielding 116.39 quintals of pods per hectare removes 87.81 kg nitrogen, 20.872 kg P2O5 and 103.905 kg K2O/ha. The effects of graded doses of nitrogen, phosphorus and potassium on plant height, leaf production, leaf area index, net assimilation rates, per cent of fruit set and other yield components were also studied.